Measuring and Analyzing Income Distribution and Income Inequality in Hungary based on Data from Personal Income Tax Returns - Ilona Kovács (Hungarian Academy of Sciences, Institute of Economics, 2010)
This study surveys various views on income distribution and income inequality and presents alternative approaches to and analytical methods of measuring income inequality. In contrast to traditional income distribution analyses, the author examines the development of income distribution and income inequality for a period between 1996 and 2004, following the change in the regime, based on personal income (consolidated income subject to general tax rates and total income including income subject to separate tax rates) declared to the Hungarian Tax and Financial Control Administration (APEH). A follow-up to this work based on similar data available up to the year 2007 is forthcoming. Based on income surveys by the Hungarian Central Statistical Office (KSH), the ratio of the income of the top tenth of the population to the bottom tenth of the population doubled from 4.6 to 9.2 between 1987 and 1997. Analyses for years following 1996 (TµRKI, Institute of Economics) show that income inequality did not increase considerably following that year; it essentially stagnated with nothing more than internal structural changes taking place. The results obtained based on data from personal income tax returns contradict these findings, as income inequality has further increased since, while the extent of income inequality itself was also considerably larger. Based on her conclusions, the author formulates important economic policy recommendations. She sees taxation, inflation, demographic changes, and changes in the structure of ownership and the way privatization took place as the leading causes behind these changes in income distribution and income inequality which were extensive by international standards.
Keywords: D31; 330; income distribution; income inequalities; Einkommensverteilung; Messung; Umverteilung; Ungarn